Levels of Students’ Critical Thinking Skills and Their Academic Achievement at Secondary Level: A Diagnostic Study - Shahzadi, Uzma; Saira (Annals of Human and Social Sciences, 2022)
The main theme of the study was to assess the levels of critical thinking skills and academic achievement of students at secondary level. The study was descriptive in nature and survey method was used to conduct the study. All the schools of district Gujrat were taken as cluster. Among all clusters 10% clusters were randomly selected. Moreover, all 10th class students of selected clusters were taken as sample for the study. Test was developed to assess students’ critical thinking skills. Students’ achievement was considered as overall score obtained by the students in the annual examination directed by Board of Intermediate and Secondary Education Gujranwala in 2021. Results of the study concluded that majority of students had high critical thinking and academic achievement level in public and private schools at secondary level. On the basis of conclusions, it was recommended that the curriculum wing may add more content in the curriculum at secondary level regarding different levels of Bloom’s cognitive domain for developing critical thinking and problem solving skills among students, as well as the administrative authorities of educational institutions may focus on the development of critical thinking skills among students to improve their learning progress and academic achievement.